PEMANFAATAN RUMAH BELAJAR LABORATORIUM MAYA UNTUK MEREMEDIASI MISKONSEPSI SISWA SMP PADA MATERI HUKUM ARCHIMEDES DI MASA PANDEMI - Febrianda Wilasari; Mohammad Budiyanto (PENSA: E-JURNAL PENDIDIKAN SAINS, 2021)
This study aimed to utilize Rumah Belajar virtual laboratory learning media to remediate the number of junior high school students' misconceptions about Hukum Archimedes, which was done for VIIIF students of SMPN 2 Bojonegoro. Experimental design was used in this study with One Group Pre-test Post-test design with a total 23 students in one class. The instrument in data collection was in the form of TTMC (Two Tier Multiple Choice). The result of data analysis showed a decrease with an average students' misconceptions of 43.04%. The result of calculation with the McNemar test showed a value of 7.12 of χ2 which was calculated on all indicators, then the result of χ2 stat > χ2 table, so there was a significant conceptual change in all indicators and the value of effect size was 2.32 (high category). It is expected that this research will be used as an alternative remedial activity to overcome the misunderstandings experienced by students.